Terminals behavior testing research under IPv6 Wi-Fi - Jie ZHANG; Qin ZHAO; Tian-le YANG (Tongxin xuebao)
As lack of essential data,carrier operators are afraid to promote IPv6 in mobile Internet due to they cannot forecast the influence of user experience.The main current mobile terminals behavior under IPv6 Wi-Fi was tested,the key point to impact user experience was analyzed and the practicability of large-scale deployment of IPv6 in mobile Internet was studied.The main steps of establishing the test platform were detailed.Test results show that the operating systems and browsers with big market share supporting for IPv6 are still not perfect.They lead to worse user experience by bad internetworking.It is the main obstacle to promote IPv6 in mobile Internet.